1981
DOI: 10.1177/002221948101400906
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Implications of Bannatyne's Recategorized WISC-R Scores for Identifying Learning Disabled Children

Abstract: This study examines the use of Bannatyne's WISC-R subtest score recategorization hierarchy in identifying students with learning disabilities. Five groups of 40 students each were selected from previously diagnosed children from each of the following categories: full-time learning disabilities placement, resource room learning disabilities placement, emotionally disturbed (ED), gifted, and educable mentally handicapped, (EMH). WISC-R subtest scores were recategorized in order to obtain Spatial, Conceptual, Seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

1983
1983
2013
2013

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 9 publications
2
4
1
Order By: Relevance
“…This study investigated the prevalence and diagnostic utility of the Bannatyne WISC-III pattern in chil-dren with LD. Similar to previous research on the Bannatyne pattern (Clarizio & Bernard, 1981;Dundon et al, 1986;Gutkin, 1979;Henry & Wittman, 1981;Kavale & Forness, 1984;Moore & Wilson, 1987;Prifitera & Dersh, 1993;Smith et al, 1977;Vance & Singer, 1979), the Bannatyne WISC-III pattern was found in 22-24 percent of children with LD. However, it missed 76-78 percent of the children previously diagnosed with a LD and incorrectly identified around 14 percent of the WISC-III normative sample as LD.…”
Section: Discussionsupporting
confidence: 89%
“…This study investigated the prevalence and diagnostic utility of the Bannatyne WISC-III pattern in chil-dren with LD. Similar to previous research on the Bannatyne pattern (Clarizio & Bernard, 1981;Dundon et al, 1986;Gutkin, 1979;Henry & Wittman, 1981;Kavale & Forness, 1984;Moore & Wilson, 1987;Prifitera & Dersh, 1993;Smith et al, 1977;Vance & Singer, 1979), the Bannatyne WISC-III pattern was found in 22-24 percent of children with LD. However, it missed 76-78 percent of the children previously diagnosed with a LD and incorrectly identified around 14 percent of the WISC-III normative sample as LD.…”
Section: Discussionsupporting
confidence: 89%
“…The results do show that this improvement is not in any way associated with differences between the two groups on the Bannatyne WISC categories. This finding would support the conclusions of Henry and Wittman (1981) who compared the recategorised WISC scores of five groups of children with varying special learning needs and reported that Bannatyne's pattern was of little value in differentiating between students with learning disabilities and those without.…”
Section: Discussionsupporting
confidence: 82%
“…Of some interest are the WISC-R factor scores (Kaufman, 1975). Similar to other samples of children with learning and attention problems (Henry & Wittman, 1981; Hodges, Borwitz & Kline, 1982), scores on the Freedom from Distractibility (FD) factor were much lower than scores on the other factors. Predictors of the variance in FD scores in this sample are reported elsewhere (Bowers, Steffy, & Swanson, 1985).…”
Section: Methodsmentioning
confidence: 51%